Investigation of the Effect of Folic Acid on Ethosuximide in Pentylenetetrazole-Induced Acute Seizures in Mice - Arzuhan ÇETİNDAĞ ÇİLTAŞ; Bilal ŞAHİN (Ahi Evran Medical Journal, 2022)
Purpose: Epilepsy is one of the most prevalent neurological diseases today. Despite various treatments, there is still no complete seizure control. Studies have shown the positive effects of folic acid (FA) and its derivatives on seizures. The objective of this study is to investigate Caspase-3 and TOS activity in brain tissues as well as the effect of folic acid on ethosuximide (ETX) in mice with pentylenetetrazol-induced seizures.